2013
DOI: 10.1128/jcm.01835-13
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of the FilmArray Blood Culture Identification Panel in Identification of Bacteria and Yeasts from Positive Blood Culture Bottles

Abstract: The FilmArray platform (FA; BioFire, Salt Lake City, UT) is a closed diagnostic system allowing high-order multiplex PCR analysis with automated readout of results directly from positive blood cultures in 1 h. In the present study, we evaluated the clinical performance of the FilmArray blood culture identification (BCID) panel, which includes 19 bacteria, five yeasts, and three antibiotic resistance genes. In total, 206 blood culture bottles were included in the study. The FilmArray could identify microorganis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
197
1
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(222 citation statements)
references
References 23 publications
(21 reference statements)
11
197
1
3
Order By: Relevance
“…86 In a study reported by Altun et al, the test covered all microorganisms in 91.6% of positive BC bottles, and it had the potential to identify multiple pathogens simultaneously from positive BC with polymicrobial growth. 87 This approach performs the extraction, amplification, and detection in a closed diagnostic system, minimizing contamination. It is a low-complexity system for the operator, requiring only injection of the BC sample into the pouch and starting the instrument; hence, the laboratory procedures can be performed by personnel with no training in molecular techniques.…”
Section: Filmarray ®mentioning
confidence: 99%
See 1 more Smart Citation
“…86 In a study reported by Altun et al, the test covered all microorganisms in 91.6% of positive BC bottles, and it had the potential to identify multiple pathogens simultaneously from positive BC with polymicrobial growth. 87 This approach performs the extraction, amplification, and detection in a closed diagnostic system, minimizing contamination. It is a low-complexity system for the operator, requiring only injection of the BC sample into the pouch and starting the instrument; hence, the laboratory procedures can be performed by personnel with no training in molecular techniques.…”
Section: Filmarray ®mentioning
confidence: 99%
“…86,87 The assay is based on the extraction and purification of nucleic acids from positive BC and amplification of the target genes by a reverse transcriptase first-stage PCR. 88 This simple system requires just a short hands-on time, with a total run time of ∼1 hour, and only one sample can be analyzed at a time.…”
Section: Filmarray ®mentioning
confidence: 99%
“…However, the identification of microorganisms from positive bottles with conventional methods may still take up to 48 h for many microorganisms and even longer for others, such as slow-growing bacteria and yeasts (11). Several methods have been evaluated for rapid identification of microorganisms directly from positive blood cultures (12)(13)(14). In contrast, the data on the performance of rapid microbiological methods in diagnostics of SBF are scarce.…”
mentioning
confidence: 99%
“…Th ese include matrix-assisted laser desorption/ionization time of fl ight (1), DNA hybridization (2), and polymerase chain reaction (3,4). Th e Verigene Gram-Positive Blood Culture (BC-GP) assay (Nanosphere, Inc., Northbrook, IL) is a multiplex, DNA hybridization assay that detects 3 genera, 9 species, and 3 resistance markers directly from blood cultures positive for gram-positive organisms.…”
mentioning
confidence: 99%